(untitled) (Research, Society and Development, 2024)
Palliative care is defined as a method in which the patient and their family members receive an improvement in quality of life, even after the terminal stage. Patients receiving palliative care at home are mostly supported by a family caregiver who participates throughout the process of illness and death. Some of these caregivers are illiterate, others have no academic education, or are unemployed, but many of these caregivers provide care to the patient in a palliative manner without knowing the importance and process of what palliative care truly entails. The objective is to analyze the perception of elderly caregivers regarding palliative care. The methodology used is descriptive, exploratory, and qualitative in nature. Elderly caregivers registered in the "Better at Home" program who were available at the time of data collection and had at least six months of experience in this type of care, were included in the study, as this timeframe allows for some experience in this care practice. Exclusion criteria included those with cognitive deficits that made it impossible to respond to the research questions. The study involved 10 caregivers of elderly people in palliative care. Out of this number, 02 refused to participate for personal reasons. This research ensures all ethical and legal aspects involving human subjects, ensuring dignity and moral and ethical respect between the researcher and the study participants. Additionally, as results and discussions, this research provided the sociocultural characterization of each caregiver, addressing the following parameters: gender, age group, education, profession, and kinship. From the data collected, it was noticed that sociocultural factors directly influence the approach to care by caregivers in palliative care. The study also explored the caregivers’ perspective on palliative care; spirituality in the context of caregiving; the affectionate relationship between the caregiver and the elderly in palliative care; and the main challenges faced by the caregiver. Thus, this study revealed the need for attention not only to the patients but also to the caregivers, to identify their needs, as they are highly vulnerable to work overload and suffering, posing risks to their physical and mental health.